A study on promotional strategy to enhance the perfomance of Zakat's collection in Melaka / Shahriyah Hj.Sha'ari - Hj.Sha'ari, Shahriyah (Faculty of Business Management, 1999)
The research paper has found out that the Malacca Zakat Centre (PZM) although had made efforts to increase collection of Zakat through various promotional activities such as talks (ceramah), exhibitions and phamplets to Zakat payers both in the government and private sectors as well as by having facilities of payment counters in the banks in Malacca such as with BBMB, BSN, BIMB and Maybank, it still did not much achieve the targeted collection amount of the Zakat. There seemed to be leakages and the availability of the facilities was not sufficient enough. The survey result clearly indicated that PZM should now make focus on Zakat collection more to the prospective Zakat payers i.e. the income earners not only in the government sector but also the private sector. This would help to increase the amount of Zakat collection. This was proved by the hypothesis I , saying that “most prospective Zakat payers in the income earner group did not pay Zakat on income” held true. The lack of facilities as the major reasons to most of the prospective Zakat payers for not paying the Zakat was not also proved to be true as shown in the hypothesis III in the report. PZM had intensively and adequately provided such physical facilities to pay Zakat by appointing collection agents in the bank counters through the signed MOU with a number of well-known banks in Malacca. It was identified that the lack of PZM's efforts to aggressively promote these facilities were the main cause of the lower level of awareness of most of the publics towards the use of these facilities. Promotional efforts through talks, phamplets, exhibitions and bill-boards at the banks can help increase this level of public awareness. The research paper also further identified the importance of promotional efforts to be stressed in order to achieve the amount of Zakat collection targeted. The PZM should promote straight to the right group i.e. the income earners in both the government and private sectors. However more focus should be to the private sectors as these groups were much neglected before. Finally, through the promotional efforts of talks PZM staff can effectively play a role to explain and highlight the Zakat payment through the salary deduction scheme as this is less burden some on the Zakat payers as compared to paying in lump sum at the end of the year. For this scheme to be successfully implemented PZM need to get the close cooperation of the employers.